MANAJEMEN KURIKULUM DAN PEMBELAJARAN ERA DISRUPTIF - Lisliana, Lisliana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The research is aimed to describe the activities of curriculum management and disruptive learning in Madrasah Aliyah Negeri 1 Banyuasin. This management activity is the initial preparation to face the disruptive era that is starting to reach the world of education, because this era requires madrasah stake holders to innovate more in carrying out digital-based learning processes. This activity includes planning, implementing, and controlling through evaluation. This research is a phenomenological research with a qualitative approach. The subjects of this study were the educators and XII class of Madrasah Aliyah Negeri 1 Banyuasin. Research data collection through three main sources, namely: direct observation (observation), document analysis, and interviews. To improve data accuracy, researchers used source triangulation and data analysis using the interactive analysis technique of the Miles and Huberman models. This study has findings, namely: first, the Mathematics Teacher of class XII conducts curriculum planning and learning activities by analyzing the needs of students and adjusting the conditions of the madrasa. In addition, the teacher also prepares learning objectives, teaching materials, strategies, learning resources, and appropriate learning media such as the use of the Whats App application as a communication medium for teachers and students outside the classroom. Keywords— Curriculum Management Mathematics Disruptive Era Abstrak— Penelitian ini bertujuan untuk mendeskripsikan kegiatan manajemen kurikulum dan pembelajaran era disruptif di Madrasah Aliyah Negeri 1 Banyuasin. Kegiatan manajemen ini merupakan persiapan awal menghadapi era disruptif yang mulai menjangkau dunia pendidikan, karena era ini menuntut stake holders madrasah untuk lebih berinovasi dalam menyelenggarakan proses pembelajaran berbasis digital. Kegiatan ini mencakup perencanaan, pelaksanaan, dan pengendalian melalui evaluasi. Penelitian ini merupakan penelitian fenomenologi dengan pendekatan kualitatif. Subjek penelitian ini adalah tenaga pendidik dan peserta didik kelas XII. Pengumpulan data penelitian melalui tiga sumber pokok, yaitu: pengamatan  langsung (observasi), analisis dokumen, dan wawancara. Untuk meningkatkan akurasi data, peneliti menggunakan triangulasi sumber dan analisis datanya menggunakan teknik analisis interaktif model Miles dan Huberman. Penelitian ini memiliki temuan, yaitu: pertama, Guru Matematika kelas XII melakukan kegiatan perencanaan kurikulum dan pembelajaran dengan menganalisis kebutuhan peserta didik dan menyesuaikan kondisi madrasah. Selain itu, guru tersebut juga  mempersiapkan tujuan pembelajaran, materi ajar, strategi, sumber belajar, dan media  belajar yang tepat seperti penggunaan aplikasi Whats App sebagai media komunikasi guru dan peserta didik di luar kelas. Kata Kunci— Manajemen Kurikulum Matematika Era Disruptif